Feasible Planning of a Medium-Tension Electric network that Meet the Development Trend of Do Luong District - Đặng Quang Khoa (Journal of Technical Education Science, 2007)
Together with the quick development of national economy in the fields such as security, national defense, industrial-agricultural production, services, tourism, etc. the demand of electricity consumption of Do Luong district, Nghe An province, is getting markedly increased. The study to evaluate the development of additional charge and the planning of medium-tension electric network that suits the socio-economic development of Do Luong district are very necessary, scientifically and practically meaningful. The thesis focuses on the following contents: evaluating the status quo of medium-tension electric network of Do Luong district; giving forecast the development of electric additional charges in the future; proposing specific planning solutions for medium-tension electric network of Do Luong district; evaluating quality of electric supply after planning.